2005
DOI: 10.1111/j.1399-6576.2005.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive end‐expiratory pressure improves arterial oxygenation during prolonged pneumoperitoneum

Abstract: The application of a constant positive airway pressure of 5 cmH(2)O preserves arterial oxygenation during prolonged pneumoperitoneum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 11 publications
4
70
0
1
Order By: Relevance
“…9,10 Despite definitive evidences that ventilator-induced lung injury may play a role when ventilating normal lungs (as generally done during anesthesia) are lacking, 11 the hypothesis that a lungprotective ventilatory strategy should be applied during general anesthesia is sound and widely debated. 1,6,7,[12][13][14] Several ventilatory strategies aiming at improving arterial oxygenation and respiratory mechanics during laparoscopic surgery have been investigated: the application of positive end-expiratory pressure (PEEP) has been shown to counterbalance the diaphragm cranial shift increasing functional residual capacity and decreasing respiratory system elastance (E RS ). 12,13,[15][16][17] Recently, translating the concept of lung-protective ventilatory strategy from the adult respiratory distress syndrome context, 9,14,[18][19][20] the application of an "open lung" strategy consisting in a recruiting maneuver (RM) followed by the subsequent application of PEEP has been suggested to effectively reexpand pneumoperitoneum-induced atelectasis and improve oxygenation during laparoscopic surgery.…”
Section: Effects Of Recruitment Maneuver and Positive End-expiratory mentioning
confidence: 99%
“…9,10 Despite definitive evidences that ventilator-induced lung injury may play a role when ventilating normal lungs (as generally done during anesthesia) are lacking, 11 the hypothesis that a lungprotective ventilatory strategy should be applied during general anesthesia is sound and widely debated. 1,6,7,[12][13][14] Several ventilatory strategies aiming at improving arterial oxygenation and respiratory mechanics during laparoscopic surgery have been investigated: the application of positive end-expiratory pressure (PEEP) has been shown to counterbalance the diaphragm cranial shift increasing functional residual capacity and decreasing respiratory system elastance (E RS ). 12,13,[15][16][17] Recently, translating the concept of lung-protective ventilatory strategy from the adult respiratory distress syndrome context, 9,14,[18][19][20] the application of an "open lung" strategy consisting in a recruiting maneuver (RM) followed by the subsequent application of PEEP has been suggested to effectively reexpand pneumoperitoneum-induced atelectasis and improve oxygenation during laparoscopic surgery.…”
Section: Effects Of Recruitment Maneuver and Positive End-expiratory mentioning
confidence: 99%
“…A 5-cmH2O PEEP diminishes intrapulmonary shunt and improves oxygenation in the presence of pneumoperitoneum (71). EIT confirmed that PEEP augments ventilation in the dependent lung zones during pneumoperitoneum (30,72).…”
Section: Alveolar Recruitment and Peepmentioning
confidence: 57%
“…The importance of PEEP application for maintaining adequate gas exchange while preventing ventilator-induced lung injury is especially emphasized (7,10,22,23). Many studies suggested that PEEP and the alveolar recruitment maneuver application improved ventilation-perfusion and gas exchange (7,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, several ventilation strategies including volume control ventilation, pressure control ventilation, recruitment maneuvers, and PEEP application are discussed for the management of ventilation and oxygenation problems caused by increased intraabdominal pressure and head-down position (19)(20)(21)(22)(23). The importance of PEEP application for maintaining adequate gas exchange while preventing ventilator-induced lung injury is especially emphasized (7,10,22,23).…”
Section: Discussionmentioning
confidence: 99%